Pelatihan Penulisan Karya Ilmiah Bentuk PTK bagi Guru di SD Muhammadiyah Pahandut Kota Palangkaraya - Iwan Fauzi; Dina Mardiana (IKIP PGRI Bojonegoro, 2021)
The Community Stimulus Partnership Program which is so-called PKMS is one of scheme of community service activity in the university carried out by the lecturer team from FKIP of the University of Palangka Raya. This PKMS program was implemented to ten classroom teachers at SD Muhammadiyah Pahandut, Kota Palangka Raya by the aim of assisting the teachers to fulfill the pedagogical competence in making improvement to their learning problems in the classroom through the reflective action which was arranged into a classroom action research (CAR). The lecturer team carried out a training and mentoring activity of writing scientific papers of CAR-based for classroom teachers at the SD Muhammadiyah Pahandut. The implementation of training method was conducted through developing of training materials, mentoring and assisting activities during the application of the classroom action. The result of the program can increase teachers’ knowledge about the basic concepts of writing scientific papers of CAR-based and increase teachers’ competence in taking reflective action to improve the quality of teaching in the subject of Indonesian Language. It is indicated by the evaluation result in observation regarding with teachers’ activities and performance during training and mentoring which reached a score 84.3 in average.Program Kemitraan Masyarakat Stimulus (PKMS) merupakan salah satu skim dalam kegiatan pengabdian kepada masyarakat di perguruan tinggi, yang dilaksanakan oleh Tim Dosen FKIP dari Universitas Palangka Raya (UPR). Program PKMS dilaksanakan kepada sepuluh orang Guru Kelas di SD Muhammadiyah Pahandut Kota Palangkaraya dengan tujuan untuk membantu memenuhi kompetensi pedagogik Guru Kelas dalam melakukan perbaikan pada permasalahan pembelajaran di kelasnya melalui tindakan reflektif yang disusun ke dalam sebuah penelitian tindakan kelas (PTK). Tim Dosen melaksanakan sebuah kegiatan pelatihan dan pendampingan penulisan karya ilmiah bentuk PTK kepada Guru Kelas di SD Muhammadiyah Pahandut. Penerapan metode pelatihan dilaksanakan melalui pendalaman materi dan kegiatan pendampingan saat implementasi tindakan kelas. Hasil kegiatan pada program PKMS ini dapat meningkatkan pengetahuan guru tentang konsep dasar penulisan karya ilmiah bentuk PTK serta meningkatkan kompetensi guru dalam melakukan tindakan reflektif untuk meningkatkan kualitas pembelajaran di kelas pada muatan pelajaran Bahasa Indonesia. Hal itu ditunjukkan dengan nilai pengamatan terhadap aktivitas dan kinerja guru saat pelatihan dan pendampingan, yakni rata-rata 84,3.